The Paradox of a Phagosomal Lifestyle: How Innate Host Cell-Leishmania amazonensis Interactions Lead to a Progressive Chronic Disease - Carneiro, Matheus B.; Peters, Nathan C. (Frontiers in Immunology, 2021)
Intracellular phagosomal pathogens represent a formidable challenge for innate immune cells, as, paradoxically, these phagocytic cells can act as both host cells that support pathogen replication and, when properly activated, are the critical cells that mediate pathogen elimination. Infection by parasites of the Leishmania genus provides an excellent model organism to investigate this complex host-pathogen interaction. In this review we focus on the dynamics of Leishmania amazonensis infection and the host innate immune response, including the impact of the adaptive immune response on phagocytic host cell recruitment and activation. L. amazonensis infection represents an important public health problem in South America where, distinct from other Leishmania parasites, it has been associated with all three clinical forms of leishmaniasis in humans: cutaneous, muco-cutaneous and visceral. Experimental observations demonstrate that most experimental mouse strains are susceptible to L. amazonensis infection, including the C57BL/6 mouse, which is resistant to other species such as Leishmania major, Leishmania braziliensis and Leishmania infantum. In general, the CD4+ T helper (Th)1/Th2 paradigm does not sufficiently explain the progressive chronic disease established by L. amazonensis, as strong cell-mediated Th1 immunity, or a lack of Th2 immunity, does not provide protection as would be predicted. Recent findings in which the balance between Th1/Th2 immunity was found to influence permissive host cell availability via recruitment of inflammatory monocytes has also added to the complexity of the Th1/Th2 paradigm. In this review we discuss the roles played by innate cells starting from parasite recognition through to priming of the adaptive immune response. We highlight the relative importance of neutrophils, monocytes, dendritic cells and resident macrophages for the establishment and progressive nature of disease following L. amazonensis infection.